2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5614520
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen effect on negative fixed charges of Al<inf>2</inf>O<inf>3</inf> passivation film in crystalline Si solar cells

Abstract: We demonstrated the electrical evolution of the AlO, AlN, and AlON and the nitrogen (N) effect on negative fixed charges, which is responsible for the reduced positive charge traps of Al2O3 passivation films in crystalline Si solar cells. The AlO and AlN deposited by RF sputtering system were served as reference samples, and the AlON prepared by a nitrogen plasma exposure was served as controlled sample. The electrical properties of these samples were demonstrated through high-low (HL) capacitance-voltage (C-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Several studies have reported that silicon oxynitride (SiO x N y ) film presented better electrical properties than the silicon oxide in various aspects, for example, when it was used as a gate dielectric in a metal–insulator–semiconductor (MIS) structure. , Researchers also found that the amorphous zinc oxynitride (ZnO x N y ) was a promising semiconductor that presents both high device performance and stability. Apart from that, aluminum oxynitride (AlO x N y ) is proven to possess distinct advantages over alumina oxide and nitride. It has been used in applications with high-k and photovoltaic fields due to its superior characteristics like lower leakage current, higher breakdown voltage, and outstanding passivation quality . Other oxynitrides (ZrO x N y , SnO x N y , TaO x N y ) also present optical, electrical, or electrochemical properties in different applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that silicon oxynitride (SiO x N y ) film presented better electrical properties than the silicon oxide in various aspects, for example, when it was used as a gate dielectric in a metal–insulator–semiconductor (MIS) structure. , Researchers also found that the amorphous zinc oxynitride (ZnO x N y ) was a promising semiconductor that presents both high device performance and stability. Apart from that, aluminum oxynitride (AlO x N y ) is proven to possess distinct advantages over alumina oxide and nitride. It has been used in applications with high-k and photovoltaic fields due to its superior characteristics like lower leakage current, higher breakdown voltage, and outstanding passivation quality . Other oxynitrides (ZrO x N y , SnO x N y , TaO x N y ) also present optical, electrical, or electrochemical properties in different applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in applications with high-k 17 and photovoltaic fields 8 due to its superior characteristics like lower leakage current, 18 higher breakdown voltage, 19 and outstanding passivation quality. 20 Other oxynitrides (ZrO x N y , 21 SnO x N y , 22 TaO x N y 23 ) also present optical, electrical, or electrochemical properties in different applications.…”
Section: Introductionmentioning
confidence: 99%
“…The oxynitride in the interface of the sample nitrided at 400 W, in fact, was very noticeably increased. This phenomenon, which has been linked to the change of interfacial bonds resulting from the reduction of interfacial defects, can enhance surface passivation [9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…The structure of Al 2 O 3 /SiNx passivation experience plasma exposure on the Al 2 O 3 passivation layer in PECVD. Nitridation of films by nitrogen and ammonia plasma exposure has often been employed in the solar cell and semiconductor device field [9,10]. AlON films can form in a similar way at the Al 2 O 3 /SiNx interfacial layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation